2020
DOI: 10.1099/jmm.0.001269
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of parechovirus A1, A3 and A4 antibodies in Yamagata, Japan, between 1976 and 2017

Abstract: Introduction. Although new parechovirus A (PeVA) types, including parechovirus A3 (PeVA3) and PeVA4, have been reported in this century, there have not yet been any seroepidemiological studies on PeVA over a period of several decades. Hypothesis/Gap Statement. The authors hypothesize that PeVA3 and PeVA4 emerged recently. Aims. The aim was to clarify changes in the seroprevalence of PeVA1, PeVA3 and PeVA4. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…A total of 62 PeVA1 strains were isolated in Yamagata between 2001 and 2021 from young children; 31 from 0‐year‐olds, 25 from 1‐year‐olds, 2 from 2‐ or 3‐year‐ olds, and 3 from 4‐, 5‐ or 6‐year‐olds, respectively (Supporting Information: Table ). These findings, and our previous seroepidemiological studies showing high NT‐Ab positive rates in young children, indicated that residents in Yamagata have been infected with PeVA1 at a young age 10,11 . All PeVA1 strains in this study were isolated from children under 6 years of age with common infectious diseases.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…A total of 62 PeVA1 strains were isolated in Yamagata between 2001 and 2021 from young children; 31 from 0‐year‐olds, 25 from 1‐year‐olds, 2 from 2‐ or 3‐year‐ olds, and 3 from 4‐, 5‐ or 6‐year‐olds, respectively (Supporting Information: Table ). These findings, and our previous seroepidemiological studies showing high NT‐Ab positive rates in young children, indicated that residents in Yamagata have been infected with PeVA1 at a young age 10,11 . All PeVA1 strains in this study were isolated from children under 6 years of age with common infectious diseases.…”
Section: Discussionsupporting
confidence: 78%
“…15,16 On the other hand, previous seroepidemiological studies between 1978 and 2017 in Yamagata suggested that PeVA1 had been in circulation stably over several decades, as a high neutralizing antibody (NT-Ab)-positive rates (more than 88% in residents 6 years or older) were found during the study period. 10,11 These seroepidemiological studies also provided the basis for our hypothesis that there had been no major change in PeVA1 antigenicity for a long time. Furthermore, our previous studies of enterovirus A71 (EV-A71) and coxsackievirus A6 (CV-A6) indicated that there was cross-antigenicity among different genomic lineages and/or subgenogroups including the prototype strain and recent Yamagata strains.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Serum samples were collected from residents in Yamagata, from whom informed consent was obtained (either from the individual or guardian) from 2000, and from those without informed consent before 2000, when the need for informed consent was not yet strictly applied. In this study, serum specimens collected in 1976, 1985, 1999, 2009, and 2019, most of which were used in our previous seroepidemiological study against parechoviruses, 20 were used and the numbers enrolled for each year in each age group are shown in Table 1. This study was approved by the Ethics Committee of the Yamagata Prefectural Institute of Public Health (YPIPHEC 20‐03).…”
Section: Methodsmentioning
confidence: 99%
“…NT Ab titers were measured in a similar manner to our previous studies using microneutralization testing 20 . Briefly, the Yamagata representative CV‐A21 strain “1652‐Yamagata‐2019,” whose sequence was registered under GenBank accession number LC533361 in our previous study, 17 was used as the challenge virus antigen and RD‐18S cell line was used.…”
Section: Methodsmentioning
confidence: 99%